Study guides

☆☆

Q: How do you factor 2x squared plus x minus 6?

Write your answer...

Submit

Related questions

(2x-3)(x-1)

(x - 1)(2x - 9)

(x - 2)(2x + 7)

(2x - 1)(2x + 5)

There is no rational factorisation.

(x - 2)(2x - 3)

(2x - 9)(2x - 9) or (2x - 9)2

2x(2x - 1)

-x2+2x

2x squared - 5x - 3 = (2x +1)(x -3)

(x + 3)(3x - 2)

7x2 -4x -5x2 +2x = 2x2 -2x

(4x - 3)(2x + 3)

(2x - 1)(5x + 8)

(x - 1)(5x + 7)

(2x - 1)(4x + 1)

(x - 2)(2x + 3)

(2x - 1)(2x + 3)

x2+2x-120 = (x+12)(x-10) when factored

(2x-1)(2x-1) = 4x^2 -4x + 1

2x2+5x-3 = (2x-1)(x+3) when factored

2(x - 7)(x - 1)

(2x - 1)(2x + 1)

x sq equalls 36 and x equalls plus or minus 6

9x2 - 18x + 99(x2 - 2x + 1)==========